2021
DOI: 10.1007/s10126-021-10028-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Method for Fucoxanthin Production Using the Haptophyte Marine Microalga Pavlova sp. OPMS 30543

Abstract: The natural pigment fucoxanthin has attracted global attention because of its superior antioxidant properties. The haptophyte marine microalgae Pavlova spp. are assumed to be promising industrial fucoxanthin producers as their lack of a cell wall could facilitate the commercialization of cultured cells as a whole food. This study screened promising Pavlova strains with high fucoxanthin content to develop an outdoor cultivation method for fucoxanthin production. Initial laboratory investigations of P. pinguis N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…They were assessed further for eligibility based on the defined criteria: (1) inclusion of studies, specifically fucoxanthin production of microalgae involving fucoxanthin content or both growth (biomass concentration) and fucoxanthin content under different culture conditions, and the (2) exclusion of studies involving environmental studies (studies utilised fucoxanthin to analyse the microalgae community in a particular habitat). Finally, 28 articles were included in the present systematic review [ 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The information from these articles was extracted and is summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were assessed further for eligibility based on the defined criteria: (1) inclusion of studies, specifically fucoxanthin production of microalgae involving fucoxanthin content or both growth (biomass concentration) and fucoxanthin content under different culture conditions, and the (2) exclusion of studies involving environmental studies (studies utilised fucoxanthin to analyse the microalgae community in a particular habitat). Finally, 28 articles were included in the present systematic review [ 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The information from these articles was extracted and is summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies compared the fucoxanthin content of microalgae and macroalgae [ 25 , 39 , 40 ]. The fucoxanthin content of the macroalgae ranged from 0.001 to 0.356% DW [ 16 , 25 ]. Microalgae demonstrated that their fucoxanthin content is up to 100 times higher than that of macroalgae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Haptophyta), Odontella aurita [54,55], Nitzschia laevis (formerly Nitzschia amabilis) [56], and Chaetoceros neogracili (formerly Chaetoceros gracilis) (Bacillariophyta), the coccolithophore Pleurochrysis carterae (Haptophyta, Coccolithophyceae) [57], Phaeodactylum tricornutum (Bacillariophyta) [46], and the microalga strain Pavlova sp. OPMS 30543 (Haprophyta) [58].…”
Section: Fucoxanthinmentioning
confidence: 99%
“…Furthermore, the biochemical profile is rich in lipids containing eicosapentaenoic acid (EPA) and the carotenoids lutein and β-carotene, which are important compounds for nutraceutical applications (Schüler et al, 2021). On the other hand, the haptophyte Diacronema lutheri (formerly known as Pavlova lutheri) is less studied for industrial production, although being promising strains for aquafeeds and human nutrition due to high contents of EPA and docosahexaenoic acid (DHA) and pigments such as fucoxanthin, diatoxanthin or β-carotene (Guihéneuf and Stengel, 2017;Tibbetts et al, 2019;Kanamoto et al, 2021).…”
Section: Introductionmentioning
confidence: 99%